Efficacy of repeat hepatectomy versus radiofrequency ablation for recurrent hepatocellular carcinoma: a Systematic Review and meta-analysis - Meng, Qingchen; Li, Xiaohang; Lang, Hongxin (Frontiers in Oncology, 2025)
BackgroundThis article compared the efficacy and safety of repeat hepatectomy (RH) and radiofrequency ablation (RFA) for the treatment of recurrent hepatocellular carcinoma (RHCC) from multiple perspectives.MethodsWe systematically searched PubMed, Embase, Web of Science, and CNKI from January 2008 to December 2023. We collected all relevant articles and assessed the quality of the data. We analyzed the data for the primary outcomes of overall survival (OS) and disease-free survival (DFS), and secondary outcomes of postoperative complications, recurrence rate, and survival benefit. Subgroup analyses were performed for tumor diameter, patient origin, and publication date.ResultsA total of 38 studies were included, comprising 5,339 patients. OS was similar in both groups (HR: 0.92, 95% CI: 0.84–1.00, P=0.04, Z=2.02), whereas DFS was better in the RH compared with the RFA group (HR: 0.80, 95% CI: 0.75–0.86, P<0.00001, Z=6.15). The incidence of major complications was lower in the RFA compared with the RH group (OR: 5.06, 95% CI: 3.29–7.81, P<0.00001, Z=7.35), but the postoperative recurrence rate was better in the RH compared with the RFA group. There was no significant difference in postoperative mortality between the two groups, but hospital stay was longer in the RH compared with the RFA group. In subgroup analyses, both OS and DFS were superior in the RH compared with the RFA group among patients with tumors ≤3 cm diameter with no significant difference in the >3 cm-diameter group. There was no significant difference in OS between the two groups among Chinese or non-Chinse patients; however, DFS was higher in the RH compared with the RFA group among Chinese and non-Chinese patients. There was no significant difference in OS between the two groups in studies published pre-2015 or post-2015 group; however, DFS was superior in the RH compared with the RFA group for both pre-2015 and post-2015 studies.ConclusionRH may be the first-choice treatment considering the long-term prognosis of patients with RHCC; RFA may be a better alternative in terms of postoperative and economic factors. RH is associated with a better prognosis in patients with tumors ≤3 cm in diameter.